Just water for cleaning baby? A cross-sectional survey of the newborn skin cleansing practices of parents in the UK. Issue 3 (June 2022) - Fleming, Sarah; Carpenter, Jane; Hunter, Louise
Abstract: Globally, 5–30% of children have eczema which could be partly attributable to skin cleansing routines. Evidence-based international guidance on this topic is lacking and dated national UK guidelines may not reflect best practices. We conducted a mixed method, UK-wide (England, Scotland, Northern Ireland and Wales) cross-sectional survey to investigate parental cleansing of their newborn's skin; 973 responses were suitable for inclusion. Sixty percent (60%) of participants delayed the first cleansing after birth for 48 h and 79.4% of participants cleansed their newborn's nappy area with each change. Participants from Scotland were more likely to cleanse their newborn within the first 48 h (X2 2 = 29.3, p < 0.001) and then cleanse more frequently (X2 4 = 14.51, p < 0.006) than those in England and Wales. 59.7% of participants used water alone for cleansing their newborn's body. Further research is needed into the appropriateness and effectiveness of parents' newborn skin cleansing practices and influences on their decision-making.